P1-S6.24 Estimation of prenatal screening rates for chlamydia, syphilis, and HIV among low-income women, California, 2007. (10th July 2011) - Chow, J; Wright, G; Bolan, G
Abstract : Background: Prenatal screening for chlamydia (CT), syphilis, and HIV infection is recommended to diagnose and treat infection that might otherwise be transmitted to the neonate and result in perinatal complications. Assessment of screening is important for programs serving low-income women who may be more likely to initiate care late in pregnancy and may be at higher risk for adverse perinatal outcomes. Methods: We analysed Medi-Cal program claims to identify low-income California female clients who delivered an infant in 2007 with ≥9 months Medi-Cal eligibility, ≥1 prenatal and family planning claim in the 42 weeks before delivery. Test claims in Medi-Cal and family planning claims during this period for CT, syphilis (including obstetric panels), and HIV were identified based on Common Procedural Terminology-4 codes. We estimated the percent of women screened for CT, syphilis, and HIV, and stratified by trimester screened, age (≤25 years; >25 years), and race/ethnicity. Results of 181 390 Medi-Cal clients who delivered in 2007, the percent with ≥1 prenatal test for all 3 STDs was 62% and for CT, syphilis, and HIV was 73%, 77%, and 62%, respectively, with little variation by age and race/ethnicity. Among 125 444 women who initiated care in the first trimester the percent tested for CT, syphilis, and HIV was 78%, 83%, and 68%, respectively. Among 11 802 women who initiated care in the third trimester the percent tested for CT, syphilis, and HIV of was lower at 43%, 48%, and 31%. Among women who were tested in the first trimester, the percent re-tested in the third trimester for CT, syphilis and HIV was 21%, 30%, and 5%, respectively. Conclusions: These lower than expected STD prenatal screening rates should be considered minimum estimates. Estimates have not included testing from all other healthcare programs accessed by women prior to delivery in the Medi-Cal program and have not been validated against medical records. Nevertheless, the lower rates of testing among women with late prenatal care initiation and the relatively low rates of HIV testing as compared with syphilis testing despite legislative mandate are concerning and further studies are needed to understand reasons for these differential rates.